Developing a business start-up model for technopreneurs - Ahamat, Amiruddin; Koh, Grace Wen Sin (Inderscience Publishers, 2022)
A business model is critical in assisting a technopreneur to start up their business. This study proposes a framework for developing a start-up business model that contains the elements of a business model for the design of a new venture. The objective of the research is to identify the changes in the environment that affect the development of the business model. The study employs qualitative research, which applies an inductive approach to the construction of theories. A series of interviews with technopreneurs from Melaka and Selangor were conducted to examine the best business model for the new technology. This study has shown the changes in the environment that would trigger business model innovation. Hence, this research came up with a business model that had nine parts. These parts were product or service, target market, customer relationship, resource or competence, process or activity, external partner, distribution channel, revenue and cost structure.